2019
DOI: 10.1002/path.5319
|View full text |Cite
|
Sign up to set email alerts
|

Integrative genomic analysis of matched primary and metastatic pediatric osteosarcoma

Abstract: Despite being the most common childhood bone tumor, the genomic characterization of osteosarcoma remains incomplete. In particular, very few osteosarcoma metastases have been sequenced to date, critical to better understand mechanisms of progression and evolution in this tumor. We performed an integrated whole genome and exome sequencing analysis of paired primary and metastatic pediatric osteosarcoma specimens to identify recurrent genomic alterations. Sequencing of 13 osteosarcoma patients including 13 prima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 71 publications
(115 reference statements)
1
37
0
Order By: Relevance
“…Though the surgery, chemotherapy, and targeted drugs offer symptomatic relief and modest improvement in survival for OS patients, the overall survival rate remains unfavourable . It is widely believed that further research on the underlying mechanisms of OS and the search for novel therapeutic targets are highly desirable to improve the prognosis of OS patients . In this study, a novel circRNA, circ_0001658, was studied for the first time, and it was demonstrated to be upregulated in OS tissues and cells.…”
Section: Discussionmentioning
confidence: 93%
“…Though the surgery, chemotherapy, and targeted drugs offer symptomatic relief and modest improvement in survival for OS patients, the overall survival rate remains unfavourable . It is widely believed that further research on the underlying mechanisms of OS and the search for novel therapeutic targets are highly desirable to improve the prognosis of OS patients . In this study, a novel circRNA, circ_0001658, was studied for the first time, and it was demonstrated to be upregulated in OS tissues and cells.…”
Section: Discussionmentioning
confidence: 93%
“…In order to better understand the genetic mechanisms of progression and evolution in HGOS, matched primary and normal samples from 13 pediatric patients with HGOS and matched metastatic or local recurrence samples of the same patients were analyzed by whole-genome sequencing and integrative analysis [13]. The data confirmed a highly heterogeneous mutational landscape including the presence of hypermutation and microsatellite instability.…”
Section: Somatic Geneticsmentioning
confidence: 97%
“…Given that HGOS has an average of 1.2 mutations per megabase, approximately 1000 samples are needed to obtain a complete catalog of the driver genes of intermediate frequencies. Results and their possible implications for the clinics have recently been reviewed and discussed [8,13].…”
Section: Somatic Geneticsmentioning
confidence: 99%
“…Among these, osteosarcoma (OS) is one of the cancer with highest mortality rate in the pediatric population [1]. In the last 35 years, there was no signi cant improvement in the ve-year survival rate if metastases are present during diagnosis [2,3]. Similar to the observation in other cancers, metastasis is a major factor for most death (75%) of OS patients [4].…”
Section: Introductionmentioning
confidence: 95%